7 - The Evolution of Accountancy to Accountability: Acknowledging Africa’s Contribution - Ackers, Barry (Africa Development, 2018)
While the primary objective of this article is to consider whether accounting has adequately responded to the expectations of contemporary society for increased corporate accountability, it simultaneously questions the Eurocentric view that attributes the development of contemporary accounting practices to Western development. Although the article links financial reporting practices to shareholder primacy, and corporate social responsibility and integrated reporting to shareholder theory, it also questions whether companies were truly embracing the fundamental principles of responsible corporate citizenship, suggesting that some companies may only be instrumentally providing non-financial reporting as a tool to entrench shareholder primacy. Without disregarding the contribution of the West to the development of accounting practices, it argues that Africa’s role, especially relating to early accounting developments, may have been deliberately ignored to perpetuate Eurocentric dogma.